The Physiological Inorganic Polymers Biosilica and Polyphosphate as Key Drivers for Biomedical Materials in Regenerative Nanomedicine - Müller WEG; Neufurth M; Wang S; Schröder HC; Wang X (International Journal of Nanomedicine, 2024)
Werner EG Müller, Meik Neufurth, Shunfeng Wang, Heinz C Schröder, Xiaohong Wang ERC Advanced Investigator Grant Research Group at the Institute for Physiological Chemistry, University Medical Center of the Johannes Gutenberg University, Mainz, GermanyCorrespondence: Werner EG Müller; Xiaohong Wang, ERC Advanced Investigator Grant Research Group at the Institute for Physiological Chemistry, University Medical Center of the Johannes Gutenberg University, Duesbergweg 6, Mainz, D-55128, Germany, Tel +49 6131 392 5791, Email wmueller@uni-mainz.de; wang013@uni-mainz.deAbstract: There is a need for novel nanomaterials with properties not yet exploited in regenerative nanomedicine. Based on lessons learned from the oldest metazoan phylum, sponges, it has been recognized that two previously ignored or insufficiently recognized principles play an essential role in tissue regeneration, including biomineral formation/repair and wound healing. Firstly, the dependence on enzymes as a driving force and secondly, the availability of metabolic energy. The discovery of enzymatic synthesis and regenerative activity of amorphous biosilica that builds the mineral skeleton of siliceous sponges formed the basis for the development of successful strategies for the treatment of osteochondral impairments in humans. In addition, the elucidation of the functional significance of a second regeneratively active inorganic material, namely inorganic polyphosphate (polyP) and its amorphous nanoparticles, present from sponges to humans, has pushed forward the development of innovative materials for both soft (skin, cartilage) and hard tissue (bone) repair. This energy-rich molecule exhibits a property not shown by any other biopolymer: the delivery of metabolic energy, even extracellularly, necessary for the ATP-dependent tissue regeneration. This review summarizes the latest developments in nanobiomaterials based on these two evolutionarily old, regeneratively active materials, amorphous silica and amorphous polyP, highlighting their specific, partly unique properties and mode of action, and discussing their possible applications in human therapy. The results of initial proof-of-concept studies on patients demonstrating complete healing of chronic wounds are outlined. Keywords: biomaterials, nanoparticles, biosilica, polyphosphate, silicatein, regenerative medicine